catena-Poly[[diaquacadmium(II)]bis(μ-pyridine-3-sulfonato)-κ2N:O;κ2O:N] - Shan-Rong Zhao; Qing-Feng Ruan; Fu-Pei Liang; Zhi-Hui Qiu (Acta Crystallographica Section E, 2008)
In the title polymeric complex, [Cd(C5H4NO3S)2(H2O)2]n, the Cd atom is located on a centre of inversion and is coordinated by two O atoms and two N atoms, derived from four different pyridine-3-sulfonate ligands, and two O atoms derived from two water molecules, forming a distorted trans-N2O4 octahedral geometry. The topology of the polymer is a one-dimensional chain mediated by bridging pyridine-3-sulfonate anions. These are connected into a three-dimensional architecture via hydrogen bonds.